Efektivitas Program Pelatihan Dalam Meningkatkan Kinerja Pada Badan Pendapatan, Pengelolaan Keuangan Dan Aset Daerah (BPPKAD) Kabupaten Gresik - Difa Aulia Salsa Bella Islami; Maulidyah Amalina Rizqi; Nur Cahyadi (Pusat Riset dan Inovasi Nasional, 2023)
In 2019-2020 employee productivity decreased and there were fluctuations in the performance assessment of Gresik Regency Regional Revenue, Financial and Asset Management Agency (BPPKAD) employees, because there were obstacles in implementing training programs which had an impact on employee performance. This research aims to analyze the effectiveness of training programs in improving performance at the Gresik Regency Regional Revenue, Financial and Asset Management Agency (BPPKAD), as well as analyzing supporting and inhibiting factors for the implementation of training programs in improving the performance of Regional Revenue, Financial and Asset Management Agency (BPPKAD) employees. ) Gresik Regency. This research is qualitative research using primary data and secondary data. Data collection techniques in this study were through interviews and observations. The selection of informants in this study was carried out using purposive sampling method. In this research, as stated by the three informants, it can be said that the implementation of the training program at the Regional Revenue, Financial and Asset Management Agency of Gresik Regency can be said to be quite effective in improving agency performance, especially in the scope of the Gresik Regency Regional Revenue, Financial and Asset Management Agency. which can be seen from several responses and results of employee performance which can be considered quite productive and good enough. There are several shortcomings in the implementation of this training program. There are obstacles in its implementation, namely in the form of budget funds spent on this training program which are considered to be insufficient due to the Covid-19 pandemic outbreak, which basically requires the implementation of this program to be minimized. One effort can be made to ensure that the implementation of the training program continues, managing the existing budget as well as possible by providing training programs to employees in accordance with the AKD (Training Needs Analysis) that has been determined, so that the budget spent is not wasted or wasted. . Apart from the Regency/City APBD, training programs can also be obtained through the bidder APBN from the ministry, Bappenas. This research contributes to employees being able to maintain a sense of responsibility in their duties where training programs are provided to obtain the skill requirements needed to carry out employee duties and have employee motivation or goals to take part in the training program. This research was only conducted on employees of the Gresik Regency Regional Revenue, Financial and Asset Management Agency (BPPKAD).